An investigation on the activation energy and the enthalpy of the primary crystallization of glass-ceramic Bi-rich BSCCOHTc superconductors - Balci, Y; Ceylan, M; Yakinci, ME (Elsevier Science Sa, 2001)
The transformation of amorphous Bi-rich BSCCO (Bi3Sr2Ca2Cu3O12-x) to a superconductive crystalline material has been characterized by structural, thermal and transport measurements. The activation energy and enthalpy data of amorphous materials are examined in terms of analysis developed for non-isothermal crystallization studies. Two groups of samples were prepared. The first group was glass pieces (8 x 8 x 2 mm(3)) of material, and the second group was the same glass material grained and powdered (similar to 1-50 Vm). Four different heating rates were used for differential scanning calorimetry and differential thermal analysis. The both thermal analysis indicated exothermic crystallization peaks at 467-489 degreesC for powdered and 472-490 degreesC for bulk samples depending on the heating rates. The enthalpy of the first crystallization of the samples varied between 40-107 and 30-35 J g(-1) powdered and bulk materials, respectively. The crystallization activation energies of the samples were found to be 299 and 349 kJ mol(-1) for powdered and bulk samples, respectively. The best electrical performance was obtained at 100 K for T-c and 90 K for T-zero. The highest thermal conductivity result was found to be 3.36 mW cm(-1) K-1. The active phonon modes of the system was also found using the Fourier transform infrared analysis. The surface and the polished cross-sections of the samples and evolution of the phases formed were examined by scanning electron microscopy. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: glass-ceramics; BSCCO superconductors; crystallization activation energy